Does bone scintigraphy show Modic changes associated with increased bone turnover?. (2020) - Järvinen, Jyri; Niinimäki, Jaakko; Karppinen, Jaro; Takalo, Reijo; Haapea, Marianne; Tervonen, Osmo
Highlights: The association between Modic changes and tracer uptake in bone scintigraphy has not previously been studied. Our results indicate that Type 1 Modic changes are associated with increased tracer uptake in bone scintigraphy. Increased bone tracer uptake reflects increased bone turnover in the area of Type 1 Modic changes. Abstract: Purpose: Our purpose was to evaluate whether Modic changes (MC) revealed in lumbar MRI are associated with increased tracer uptake shown in bone scintigraphy. To our knowledge, this has not previously been studied. Methods: We included patients with MC shown in lumbar MRI and bone scintigraphy performed within six months before or after MRI. Exclusion criteria included metastasis and other specific lesions in the area of interest such as discitis, tumors or fractures. We compared the level and type of MC to the degree of tracer uptake shown in bone scintigraphy. Tracer uptake was assessed both visually and quantitatively. We calculated the lesion-to-normal-bone ratios between the MC area with increased tracer uptake and the vertebra with normal tracer uptake. We used linear mixed models in statistical analyses. Results: Our study sample consisted of 93 patients (aged 37–86) with 299 MC (28 Type 1 (M1), 50 mixed Type 1/2 (M1/2), 3 mixed Type 1/3 (M1/3), 211 Type 2 (M2), 6 mixed Type 2/3 (M2/3), and 1 Type 3 (M3)). Of all the MC, 26 (93 %) M1, 34 (64 %) in the combined M1/2 and M1/3 group, and 11 (5 %) in the combined M2, M2/3 and M3 group showed increased tracer uptake. The mean lesion-to-normal-bone ratio was higher for lesions with a Type 1 component (M1, M1/2 and M1/3) than for other types, at 1.55 (SD 0.16) for M1; 1.44 (SD 0.21) for combined M1/2 and M1/3; and 1.28 (SD 0.11) for combined M2, M2/3 and M3; p = 0.001). Conclusion: In most cases, MC with a Type 1 component showed increased tracer uptake in bone scintigraphy. This indicates that bone turnover is accelerated in the M1 area.